Sanksi Pidana terhadap Pelaku yang Melakukan Kampanye Pemilu di Media Massa selama Masa Tenan - I Dewa Ketut Alit Catur Mahaputra; I Nyoman Gede Sugiartha; Indah Permatasari (Jurnal Preferensi Hukum, 2025)
Campaigns in the modern era have evolved following technological advances. Social media is one of them, now many candidates for people's representatives are campaigning through social media, campaigns carried out through social media no longer ignore the quiet period, even though the Law has expressly stipulated criminal provisions for anyone who violates it. The formulation of the problem obtained is how is the regulation of election campaigns in Indonesia, and how are the criminal sanctions against perpetrators who conduct election campaigns in the mass media during the quiet period. This research uses normative legal research with a statutory approach and conceptual approach. The results of the discussion show that the regulation of election campaigns in Indonesia has been regulated in Law Number 7 of 2017 concerning General Elections, as well as criminal sanctions against perpetrators who conduct election campaigns in the mass media during the quiet period are regulated in Article 287 paragraph (5) Jo Article 492 of the General Election Law, which will be punished with a maximum imprisonment of 1 (one) year and a maximum fine of Rp12,000,000.00 (twelve million rupiah).